The Effect of Transformational Leadership Style and Career Development on Organizational Performance With Work Motivation as An Intervening Variable at PT. PLN (Persero) UP3 Jember (Pusat Riset dan Inovasi Nasional, 2025)
PT. PLN (Persero) UP3 Jember has a strategic role in maintaining the reliability of electricity supply and service quality. However, in 2024 there was a gap between the target and the realization of network maintenance without blackouts, which indicates fluctuations in organizational performance. This study aims to analyze the effect of transformational leadership style and career development on organizational performance, both directly and through work motivation as an intervening variable. The study used a quantitative approach with a survey method of 33 employees in managerial positions using a saturated sampling technique. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression and the Baron and Kenny mediation model. The results showed that trans-formational leadership and career development had a positive and significant effect on work motivation and organizational performance. In addition, work motivation was proven to have a significant effect on performance and acted as a partial mediator. In conclusion, improving leadership quality and a transparent career development system can encourage work motivation and improve organizational performance at PT. PLN (Persero) UP3 Jember.